Tuber indicum colonization enhances plant drought tolerance by modifying physiological, rhizosphere metabolic and bacterial community responses in Pinus armandii - Huang, Lanlan; Wan, Shanping; Liu, Yong; Zhan, Jian; Zhang, Faming; Yang, Hui; Zhang, Fengming; Xie, Xuedan; Shi, Xiaofei; Wang, Yanliang; Yu, Fuqiang (Frontiers in Plant Science, 2025)
Tuber indicum has been extensively investigated in the fields of ecology, mycorrhizal synthesis with various plant species, and cultivation. Its impacts on plant physiological and metabolic responses under different water regimes remain unclear. Here, T. indicum colonized Pinus armandii seedlings were used to assess plant physiological responses, rhizosphere metabolomic profiles, and microbial community dynamics under differential water regimes. The results showed that T. indicum colonization significantly increased the contents of chlorophyll a and total pigments, but decreased the malondialdehyde content in the leaves under moderate drought stress. Under moderate and severe drought stresses, the diversity of the mycorrhizosphere bacterial community in the T. indicum - colonized group was significantly lower than that in the control group. Meanwhile, the bacterial community structures were similar under various drought conditions. Metabolic analysis revealed that carbohydrates and their derivatives were the most upregulated, while amino acids and their derivatives were the most downregulated differential expressed metabolites in T. indicum - colonized seedlings, compared to the control group. The relative abundance of Nocardioides albus has a significant positive correlation with trans-2-hexenal, and trans-2-hexenal shows a significant negative correlation with the malondialdehyde content and a significant positive correlation with the content of photosynthetic pigments, implying that N. albus might play an important role in regulating plant drought tolerance. Overall, these results suggest that T. indicum colonization could modulate the host plant’s physiological, mycorrhizosphere bacterial community and metabolic responses to enhance plant drought tolerance. These findings support the application of T. indicum mycorrhizal seedlings in drought-prone areas for ecological restoration and truffle cultivation.